Metformin for the treatment of breast cancer: Protocol for a scoping review of randomised clinical trials - Araujo, Carolina Fumico Massuda [UNESP]; Nunes, Lélia Cápua [UNESP]; Murta-Nascimento, Cristiane [UNESP]; Souza, Cristiano De Pádua; Bragagnoli, Arinilda Campos; Fukushima, Fernanda Bono [UNESP]; Vidal, Edison Iglesias De Oliveira [UNESP] (BMJ, 2021)
Introduction Innovation through the repurposing of generic drugs encloses several advantages when compared with the process of developing new drugs from scratch. Metformin is an established and inexpensive antidiabetic drug for which anticancer properties have been hypothesised. A systematic review of observational studies found promising results for metformin related to breast cancer in women with diabetes. Although the number of randomised clinical trials of metformin for the treatment of breast cancer increased over the last decades, the overall landscape of those studies in this heterogeneous field remains unclear. Hence, we designed the present scoping review protocol to map the literature on randomised clinical trials of metformin in the treatment of breast cancer to determine the value and scope of future systematic reviews on this subject and identify research gaps. Methods We will search MEDLINE (via PubMed), EMBASE, CENTRAL, LILACS, Web of Science and sources of grey literature. We will include any randomised clinical trial of metformin for the treatment of breast cancer in adult women, and will not impose restrictions regarding context, language or publication date. Two independent reviewers will screen and select studies, and chart the data. We will structure the presentation of our results based on the molecular types of breast cancer, their stages and treatment modalities. Ethics and dissemination As a literature review, this study is exempt from ethics approval. Findings will be disseminated through presentations in conferences and a peer-reviewed publication. Open Science Framework registration osf.io/yquba.
Keywords: breast tumours; clinical trials; epidemiology; oncology; therapeutics